Hearing, feeling or seeing a beat recruits a supramodal network in the auditory dorsal stream. (12th August 2016) - Araneda, Rodrigo; Renier, Laurent; Ebner‐Karestinos, Daniela; Dricot, Laurence; De Volder, Anne G.
Abstract: Hearing a beat recruits a wide neural network that involves the auditory cortex and motor planning regions. Perceiving a beat can potentially be achieved via vision or even touch, but it is currently not clear whether a common neural network underlies beat processing. Here, we used functional magnetic resonance imaging (fMRI) to test to what extent the neural network involved in beat processing is supramodal, that is, is the same in the different sensory modalities. Brain activity changes in 27 healthy volunteers were monitored while they were attending to the same rhythmic sequences (with and without a beat) in audition, vision and the vibrotactile modality. We found a common neural network for beat detection in the three modalities that involved parts of the auditory dorsal pathway. Within this network, only the putamen and the supplementary motor area (SMA) showed specificity to the beat, while the brain activity in the putamen covariated with the beat detection speed. These results highlighted the implication of the auditory dorsal stream in beat detection, confirmed the important role played by the putamen in beat detection and indicated that the neural network for beat detection is mostly supramodal. This constitutes a new example of convergence of the same functional attributes into one centralized representation in the brain. Abstract : There is one centralized and multisensory neural network involved in the processing of a beat, whatever detected in audition, in vision or via the vibrotactile modality. Among these regions within the auditory doesal pathway and motor planning areas, which are similarly acitivated in all three modalities, the supplementary motor area and the putamen are the most specific to the beat. See Figure 5 in the article.